Lessons From the Field: Creating Sustainable Engagement in Organizational Learning - Lyle, Ellyn (LEARNing Landscapes, 2012)
The philosophies of Join-Up with horses extend to inform theories of learner engagement. Drawing from these theories, and theories in adult education, I discuss paths to creating sustainable engagement of learners within industry-based education initiatives. Embracing a reflexive narrative approach, I consider the efforts of two large organizations to establish and grow learning cultures. Critically deconstructing these applied learning practices, and their successes and failures, reinforces my assumption that deep communication, trustful interaction, and choice are integral to the creation of meaningful and sustainable learning. This assumption leads me to consider the ways in which these philosophical commitments manifest themselves in physical learning spaces.